Human papilloma virus as a possible factor in the pathogenesis of oral lichen planus - Sayed Mohammad Razavi; Parichehr Ghalayani; Mohammad Reza Salehi; Hajar Attarzadeh; Mahdi Shahmoradi (Wolters Kluwer Medknow Publications, 2009)
Background: Oral lichen planus (OLP) is a common chronic inflammatory mucocutaneous disease. Clinical diagnosis of OLP requires clinical work-up and histologic examination to rule out possible dysplasia and carcinoma. It is possible that oral mucosal viral infections including HPV infection may have a causative role in OLP pathogenesis. The aim of this study was to examine the co-incidence of human papilloma virus type 18 and oral lichen planus. Methods: This study was a case-control study. Twenty nine paraffinized specimens of previously diagnosed oral lichen planus and 14 paraffinized specimens of nonpathogenic mucosa were studied. Polymerase Chain Reaction ( PCR) analyze used for detection of DNA HPV 18 .The data were ana-lyzed with SPSS software and Fisher's exact test was used to find the possible relation between HPV18 infection and oral lichen planus. Results: Nine out of 29 (31.0%) lichen planus samples and one out of 14 (7.1%) controls were HPV 18 positive. No significant correlation (P = 0.128) was observed between HPV18 infection and oral lichen planus. Conclusion: According to the findings there might be a coincidence of human papilloma virus type 18 and oral lichen planus.